2018
DOI: 10.1111/cyt.12612
|View full text |Cite
|
Sign up to set email alerts
|

Expression of phosphatase and tensin homologue in imprint smears of endometrial carcinoma

Abstract: Immunocytochemical findings from PTEN stain, in addition to cytomorphological features, appeared to be a useful marker in the diagnosis and in the postoperative prognosis of endometrial carcinoma in endometrial cytology with imprint smears and that high PTEN expression is related to morphological features of less aggressiveness tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…All the 11 proteins have been studied by immunohistochemistry in primary tissue specimens. Notably, MKI67 and PTEN were also validated in tissue samples from imprint smears [51][52][53], as well as CDH1, which was analyzed in uterine aspirates using mass spectrometry-based approaches [54]. MUC16 and WFDC2 have been extensively studied in serum samples by antibody-based techniques such as ELISA or chemiluminescence techniques [50,[55][56][57] and L1CAM was also validated in serum but just in one study [58].…”
Section: Prognostic Protein Biomarkers In Ecmentioning
confidence: 99%
“…All the 11 proteins have been studied by immunohistochemistry in primary tissue specimens. Notably, MKI67 and PTEN were also validated in tissue samples from imprint smears [51][52][53], as well as CDH1, which was analyzed in uterine aspirates using mass spectrometry-based approaches [54]. MUC16 and WFDC2 have been extensively studied in serum samples by antibody-based techniques such as ELISA or chemiluminescence techniques [50,[55][56][57] and L1CAM was also validated in serum but just in one study [58].…”
Section: Prognostic Protein Biomarkers In Ecmentioning
confidence: 99%
“…In vitro data have demonstrated that the PI3K-Akt signaling pathway contributes to the carcinogenesis of EC (61). A study of patients with EC observed that PTEN expression is negatively associated with myometrial invasion depth, indicating that PTEN may play an important role of in the development of EC and is potentially a prognostic indicator of EC (62). It has been reported that metformin inhibits Akt expression and stimulates PTEN and IP3 expression via inhibition of the PI3K-Akt signaling pathway (63).…”
Section: Metformin Directly Inhibits the Development Of Ecmentioning
confidence: 99%